2012
DOI: 10.1177/0961203311434937
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine imbalance in systemic lupus erythematosus: a study on northern Indian subjects

Abstract: This study showed a distinct profile of cytokine imbalance in patients with SLE from the northern plains of India. The levels, ratios and correlations of cytokines in patients suggested significant deviation from normal. Correlations of cytokines with SLEDAI scores indicated that TNF-α contributes significantly to the pathological manifestations of SLE in patients from the region. A detailed study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…Similarly to our data, Tabarkiewicz et al 27 also showed that increased plasma IL‐17 concentrations were associated with severity in SLE patients. Finally, in accordance with others studies, we also found that increased levels of IL‐10 (a Treg cytokine) strongly predicted SLE and severity of the illness 20 , 28 . This cytokine may play a key role in the pathogenesis of SLE because IL‐10 enhances antibody secretion, regulates growth and differentiation of B‐cells and blunts T‐cell activation and TNF‐α secretion.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to our data, Tabarkiewicz et al 27 also showed that increased plasma IL‐17 concentrations were associated with severity in SLE patients. Finally, in accordance with others studies, we also found that increased levels of IL‐10 (a Treg cytokine) strongly predicted SLE and severity of the illness 20 , 28 . This cytokine may play a key role in the pathogenesis of SLE because IL‐10 enhances antibody secretion, regulates growth and differentiation of B‐cells and blunts T‐cell activation and TNF‐α secretion.…”
Section: Discussionsupporting
confidence: 91%
“…Herein, the level of IL-4 was compared with the controls as reported in previous studies [20,27]. Also, it has been found that the percentage of IL-4+ cells within the CD4+T-cells from SLE patients is not statistically different in comparison to healthy controls [14].…”
Section: Discussionmentioning
confidence: 96%
“…Plasma levels of IL-10 were consistently reported to be increased in SLE [8,19,27,28]. It has been found to be over produced by the B cells and monocytes [29].…”
Section: Discussionmentioning
confidence: 97%
“…However, in MRL/lpr mice, an increased expression of TNF was observed in the serum and in the kidney tissue (35). Human studies involving adult patients showed increased serum levels of TNF with (10,11) or without (36) association with disease activity. Another study presented high levels of TNF in patients with inactive disease, suggesting a protective effect of this cytokine in SLE (9).…”
Section: Discussionmentioning
confidence: 99%